(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The ERC ARTIVISM project focuses on various art forms used by activists in order to formulate political claims. From a multisensory perspective, creativity and performance as subversive forms of political expression are researched in super-diverse cities on three continents (Douala and Yaoundé in Cameroon, Los Angeles in the United States of America, Genova and Viareggio in Italy and Nice and Marseille in France). Applying the event approach instead of a group-centred perspective, the team has elaborated on methods of apprenticeship, field-crossing and audio-visual anthropology (filming, drawing). Preliminary results indicate the growing importance of speculation, touristification and city-marketing as targets chosen by activists who organise independent carnival and carnivalesquepolitical performances in a context of securisation, control and censorship.